Effects of the stone density on the outcome of percutaneous nephrolithotomy in pediatric population - Kısa, Erdem; Uçar, Murat; Yücel, Cem; Süelözgen, Tufan; İlbey, Yusuf Özlem (Journal of Surgery and Medicine, 2019)
Aim: The measurement of the stone densities of urinary system calculi in Hounsfield units (HU) using non-contrast computed tomography (NCCT) provides information regarding the composition and hardness of the stones. This study aims to evaluate the effects of stone HU values on the percutaneous nephrolithotomy (PCNL) outcomes in pediatric stone disease patients. Methods: In this retrospective cohort study, the records of 57 pediatric patients, who had undergone PCNL between 2010 January and 2018 May, were evaluated. Demographic data, stone characteristics, peroperative changes, outcomes, and complications were obtained from patient records. The patients were divided into two groups based on their HU values: the low HU group (HU ≤1000) and the high HU group (HU >1000). Results: A total of 61 PCNL operations were performed on 57 pediatric patients. Overall median stone size was 420 mm2 – 475 mm2 (78-2475) and simple/complex stone rate was (52.4%) / 29 (47.5%). A total of 38 patients were examined using NCCT prior to the operation. Twenty-two of the patients had an HU value ≤1000, whereas 16 had an HU value>1000. There were no statistically significant differences between the low and the high HU groups in terms of the duration of procedure, fluoroscopy time, success rates, and complications. Conclusion: PCNL surgery is an effective method for the treatment of large and complex stones in the pediatric population. We determined that in pediatric patients who were evaluated using NCCT prior to PCNL the stone HU values of did not influence PCNL success.